Biopsy Proven Tumefactive Multiple Sclerosis with Concomitant Glioma: Case Report and Review of the Literature - Golombievski, Esteban E.; McCoyd, Matthew A.; Lee, John M.; Schneck, Michael J. (Frontiers in Neurology, 2015)
We report a case of pathologically confirmed tumefactive multiple sclerosis (MS) followed shortly thereafter by the diagnosis of an oligoastrocytoma. The complexity of diagnosis and management of concomitant presence of tumefactive MS and glial cell tumors is discussed.